Effect of Cigarette Prices on Cigarette Consumption in Indonesia: Myopic and Rational Addiction Studies - Lesmana, Indra; Khoirunurrofik, Khoirunurrofik (Universitas Airlangga, 2022)
This study analyzes the effect of cigarette prices on cigarette consumption in Indonesia. By using aggregate macro data on cigarette consumption (administrative data) for 2015-2020, estimated using OLS, 2SLS, GMM, and System-GMM, we found that cigarette prices have a negative and significant effect on cigarette consumption based on myopic and rational addiction models. The estimation results also confirm that cigarettes are inelastic products where price changes do not significantly impact cigarette consumption. It implies that the Government needs to significantly increase excise rates and minimum selling prices regularly to control cigarette consumption more effectively.